THE PROBLEM BASED LEARNING (PBL)-BASED ENTREPRENEURSHIP LEARNING MODEL DEVELOPMENT TO IMPROVE THE LIFE SKILLS OF THE TEACHER TRAINING STUDENTS IN PRIVATE UNIVERSITIES THROUGHOUT SOLO RAYA - Suryanti, Hera Heru Sri (Dewantara, 2013)
Purpose ? This research aims at providing a PBL-based Entrepreneurship learning model to improve the student life skills in Private Faculties of Teacher Training and Educationin Solo Raya. Method ? This research was a ?research and development?. The research and development model consists of three steps: preliminary study, model development, and model testing. The research study stage employed a qualitative research; techniques of collecting data used were observation, interview, and content analysis and archive, while the data validation was done using data (source), method and theory triangulations, and informant review; data analysis was done using an interactive model of analysis. Findings ? The implementation of life skills education in FKIP of UNISRI was not based on specific curriculum yet; the curriculum is integrated into all courses existing in the Study Program. The life skill content of each course is different but proportional and consistent with the characteristics of the course. Life skill education was given to the students in terms of the thinking and working skill, knowledge, and attitude the students to prepare themselves as independent members of society. Significance ? The Problem Based Learning (PBL)-Based Entrepreneurship learning model development could improve the life skills of the private Teacher Training and Education Faculty?s Students throughout Solo Raya. Keyword: Model development, entrepreneurship learning, life skills.